Omentin-1 is decreased in maternal plasma, placenta and adipose tissue of women with pre-existing obesity. - Gillian Barker (Public Library of Science (PLoS), 2012)
Objective The aim of this study was to determine (i) the effect of maternal obesity and gestational diabetes mellitus (GDM) on (i) the circulating levels of omentin-1 in cord and maternal plasma, and (ii) gene expression and release of omentin-1 from human placenta and adipose tissue. The effect of pregnancy on circulating omentin-1 levels was also determined. Design Omentin-1 levels were measured in maternal and cord plasma from obese and non-obese normal glucose tolerant women (NGT; n = 44) and women with GDM (n = 39) at the time of term elective Caesarean section. Placenta and adipose tissue expression and release of omentin-1 was measured from 22 NGT and 22 GDM women collected at the time of term elective Caesarean section. Omentin-1 levels were also measured in maternal plasma from 13 NGT women at 11 and 28 weeks gestation and 7 weeks postpartum. Results Maternal obesity was associated with significantly lower omentin-1 levels in maternal plasma; however, there was no effect of maternal obesity on cord omentin levels. Omentin-1 gene expression was lower in placenta and adipose tissue obtained from women with pre-existing obesity. In addition to this, adipose tissue release of omentin-1 was significantly lower from obese pregnant women. Omentin-1 levels were significantly lower in non-obese GDM compared to non-obese NGT women. However, there was no difference in omentin-1 levels between obese NGT and obese GDM women. There was no effect of GDM on cord omentin levels, and placental and adipose tissue omentin-1 expression. Maternal omentin-1 levels were negatively correlated with fetal birthweight and fetal ponderal index. Conclusions The data presented in this study demonstrate that pre-existing maternal obesity is associated with lower omentin-1 expression in placenta, adipose tissue and maternal plasma. Alteration in omentin-1 in pregnancy may influence the development of metabolic disorders in offspring later in life.